Growing up with cerebral palsy: perceptions of the influence of family. Issue 5 (21st October 2013) - Freeborn, D.; Knafl, K.
Abstract Background Cerebral palsy (CP) is a non‐progressive condition present from birth or infancy that includes various neurological patterns of dysfunction. It is characterized by abnormal motor control and/or posture and can involve communication difficulties. Children and youth with CP face multiple social and developmental challenges during their formative years including mild to severe physical limitations, poor socialization, limited recreational activities, and stigmatization. Families play a key role in supporting adaptation to CP. The purpose of this paper was to explore women's perceptions of the ways their families contributed to their overall quality of life with CP. Methods Drawing on data from a qualitative study of eight women with CP, the purpose of this analysis was to examine perceptions of the ways in which their families and individual family members contributed to participants' overall quality of life and adaptation to CP. Respondents ranged in age from 22 years to 55 years and had varied forms of CP. The study was based on a feminist biographical approach, which combines biographical methods with feminist principles. Results Participants provided considerable, rich contextual data on their family life and the pivotal role family played. The analysis identified four themes related to supportive family roles: (1) being an advocate, and teaching advocacy; (2) promoting inclusion and acceptance; (3) integrating therapy into daily life; and (4) the importance of siblings as friends and mentors. Conclusions Health‐care providers can contribute to the family's ability to facilitate quality of life by providing guidance on how to be advocates and teach advocacy, including the child with CP in family activities, accessing therapy and incorporating beneficial therapies at home, and promoting healthy sibling relationships.